Charlie to the Rescue - Ballantyne, R. M. (Saga Egmont, 2022)
Fatherless young Charlie Brooke is a brave and kind character, who is always trying to help others. His mother is struggling to make ends meet, and when Charlie leaves school he must find a way to support them both. One fateful day Charlie encounters a shipwreck, and his brave actions in the face of much danger will change the course of his life forever. A thrilling adventure tale by Scottish author R.M. Ballantyne.